ANALISIS SPATIO-TEMPORAL PERUBAHAN TUTUPAN LAHAN DAN KAITANNYA DENGAN TEMPERATUR PERMUKAAN LAHAN DI DESA CIPUTRI PERIODE 2005-2035 - Putra, I Kadek Yoga Dwi; Manessa, Masita Dwi Mandini; Wibowo, Adi (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Land Use and Land Cover (LULC) change are major factors affecting Land Surface Temperature (LST), especially in areas experiencing urbanisation and climate change pressures. Ciputri Village, which is predominantly agricultural, has experienced significant changes in land cover patterns over the past two decades, with the potential for increased surface temperature due to land use change. This study analyses and predicts the dynamics of land use and cover changes and their relationship with land surface temperature in the period 2005-2035 using a combination of remote sensing data and Cellular Automata-Artificial Neural Network (CA-ANN) models. The analysis showed that between 2005 and 2020, the area of dense vegetation decreased by 20.49%, while built-up land increased by 43.75%. In line with these changes, surface temperature increased by 1.96°C on average. Predictions to 2035 show a similar trend, with built-up land projected to increase by 20.11%, while average surface temperature is expected to increase by 2.71°C compared to 2005. The correlation between land cover change and surface temperature variation suggests that conversion of dense vegetation to mixed land and built-up land is a major factor driving temperature increases. These findings emphasise the urgency of spatially-based climate change mitigation, including vegetation conservation and sustainable development planning to reduce the impact of future temperature increases.